Echinacoside Upregulates Sirt1 to Suppress Endoplasmic Reticulum Stress and Inhibit Extracellular Matrix Degradation In Vitro and Ameliorates Osteoarthritis In Vivo. (3rd November 2021) - Lin, Zhen; Teng, Cheng; Ni, Libin; Zhang, Zhao; Lu, Xinlei; Lou, Junsheng; Wang, Libo; Wang, Yuxin; Chen, Wenhao; Zhang, Xiaolei; Lin, Zhongke
Abstract : Background . Osteoarthritis (OA) is a progressive illness that destroys cartilage. Oxidative stress is a major contributor of OA, while endoplasmic reticulum (ER) stress is the key cellular damage under oxidative stress in chondrocytes. Echinacoside (ECH) is the main extract and active substance of Cistanche, with potent antioxidative stress (OS) properties, and currently under clinical trials in China. However, its function in OA is yet to be determined. Purpose . We aimed to explore the specific role of ECH in the occurrence and development of OA and its underlying mechanism in vivo and in vitro . Methods . After the mice were anesthetized, the bilateral medial knee joint meniscus resection was performed to establish the DMM model. TBHP was used to induce oxidative stress to establish the OA model in chondrocytes in vitro . Western blot and RT-PCR were used to evaluate the level of ER stress-related biomarkers such as p-PERK/PERK, GRP78, ATF4, p-eIF2 α /eIF2 α, and CHOP and apoptosis-related proteins such as BAX, Bcl-2, and cleaved caspase-3. Meanwhile, we used SO staining, immunofluorescence, and immunohistochemical staining to evaluate the pharmacological effects of ECH in mice in vivo . Results . We demonstrated the effectiveness of ECH in suppressing ER stress and restoring ECM metabolism in vitro . In particular, ECH was shown to suppress tert-Butyl hydroperoxide- (TBHP-) induced OS and subsequently lower the levels of p-PERK/PERK, GRP78, ATF4, p-eIF2 α /eIF2 α, and CHOP in vitro . Simultaneously, ECH reduced MMP13 and ADAMTS5 levels and promoted Aggrecan and Collagen II levels, suggesting ECM degradation suppression. Moreover, we showed that ECH mediates its cellular effects via upregulation of Sirt1. Lastly, we confirmed that ECH can protect against OA in mouse OA models. Conclusion . In summary, our findings indicate that ECH can inhibit ER stress and ECM degradation by upregulating Sirt1 in mouse chondrocytes treated with TBHP. It can also prevent OA development in vivo .